EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI JAGUNG HIBRIDA DI KECAMATAN PALOLO KABUPATEN SIGI - Made Antara (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
This research aimed to identify: (1) the efficiency level of input production (land area size, seed number, fertilizer and labors) of hybrid corn farm, and (2) the income of hybrid corn farm. The research population samples of 35 peoples were hybrid corn farmers in Bobo, Bunga and Berdikari villages taken using a random sampling method. Data was analyzed using the Cobb-Douglass production function, production input efficiency and income analysis. The results of this research showed that all variables observed significantly influenced the hybrid corn production, except labors which was relatively inefficient. The income of the hybrid corn farm was IDR 3,806,414. 19/ha/planting season.